Harmonization of Traditions in the Modern Era of Ummah: A Phenomenological Analysis of the Samin Kudus Marriage Contract - Moh Durrul Ainun Nafis (LP2M Institut Agama Islam Sunan Giri (INSURI) Ponorogo, 2021)
Within a plural society, social and cultural discourses are frequently becoming a scourge. One of them is the blending of traditions in the face of people's modernity, such as the link between Islam and the indigenous Samin's traditional beliefs. The purpose of this study is to conduct a phenomenological investigation into the Samin Kudus custom of marriage contracts. Data was gathered using descriptive techniques such as observation, documentation, and interviews, and then analyzed using Edmund Husserl's phenomenological methodology. According to the findings, the marriage contract was held between the groom and the bride through the Samin custom of the marriage contract procession. This is due to the fact that the potential groom is of Samin custom practitioners who also embraces Islam belief, whereas the bride is a Muslimah. In addition, the marital contract procession is a harmonization across traditions in the study of phenomenology, specifically in harmonizing customs and religion through the stages of nyumuk, mbalesi gunem, ngendek, and paseksen.